Clozapine re-challenge with lithium supplementation following clozapine-induced neutropenia - Md Rosli, Ahmad Nabil; Subbiah, Rakesh; Maniam, T (ASEAN Federation of Psychiatry, 2014)
Objectives: This paper aims to report on a case in which re-challenging with clozapine in combination with lithium in a patient who developed neutropenia was carried out. Methods: The patient was treated with clozapine for treatmentresistant schizophrenia. After five weeks he showed much improvement but developed neutropenia. Withdrawal of clozapine brought on a relapse of psychotic symptoms. Subsequently, clozapine was reintroduced along with Lithium. The neutrophil count was monitored closely. Results: The neutrophil and white blood cell count were noted to return to normal upon re-challenging, and the patient’s clinical condition also improved. Conclusion: Simultaneous administration of lithium and clozapine to patients experiencing neutropenia on clozapine is a possible strategy. However, very close monitoring of the white count is needed